2011
DOI: 10.1039/c1an15172j
|View full text |Cite
|
Sign up to set email alerts
|

Doped amorphous silica nanoparticles as enhancing agents for surface-assisted time-of-flight mass spectrometry

Abstract: This article examines the use of doped amorphous silica nanoparticles for surface-assisted laser desorption/ionisation-time of flight-mass spectrometry (SALDI-TOF-MS) of hydrophilic and hydrophobic compounds. A range of particles with surface aliphatic carboxylic, aminophenyl, phenyl or aminopropyl groups have been produced and these have been doped with carbon black, polyaniline or graphite. The effects of surface groups and dopants on the laser desorption/ionisation process were studied. The key factor in ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 42 publications
2
27
0
Order By: Relevance
“…The enhanced signal intensity with this powder compared with other commercial dusting agents has also been observed for drugs [8] and nicotine [9,10] in pre-dusted lifted latent fingermarks using SALDI-MS. Its effect on the spectrums of endogenous constituents in latent fingrmarks has also been described [13].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The enhanced signal intensity with this powder compared with other commercial dusting agents has also been observed for drugs [8] and nicotine [9,10] in pre-dusted lifted latent fingermarks using SALDI-MS. Its effect on the spectrums of endogenous constituents in latent fingrmarks has also been described [13].…”
Section: Discussionmentioning
confidence: 98%
“…In our experiments it is assumed that similar adsorption of the explosives onto the ROAR particles occurred rapidly to produce a complex of sufficient stability to resist evaporation of the explosives under the high vacuum conditions within the mass spectrometer and that under laser irradiation the residues present on the surface of the particles assisted ionization of the adsorbed explosives producing the negative ions detected for the nitro-organic explosives or positive ions for the peroxide explosive TATP. The mechanism for Surface Assisted Laser Desorption/Ionization of polar and non-polar analytes using these particles has recently been described [13]. The SALDI-MS of the aliphatic explosives were characterized by a lack of the de-protonated molecular ions and peaks probably due loss of nitro groups and the presence of low mass peaks at m/z 46 and/or 62 due to (NO 2 + ) and (NO 3 + ) ions, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…1(c) and (d). These observations can be explained by a proposed mechanism [42] which involves the initial adsorption of the analyte onto the particle surface. Ionic interactions enable the analyte to remain close to the particle surface.…”
Section: Amino and Fatty Acid Analysismentioning
confidence: 95%
“…In an earlier SALDI-TOF-MS study with carbon black-doped silica particles, amino acids analysed were best detected in positive ion mode and squalene was not detected in negative mode [42]. A recent review also reported that lipids were more easily detected and with greater sensitivity in positive mode than in negative mode [43].…”
Section: Amino and Fatty Acid Analysismentioning
confidence: 95%
See 1 more Smart Citation